2021
DOI: 10.1101/2021.01.04.425197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Clustering of CD68+ Tumor Associated Macrophages with Tumor Cells is Associated with Worse Overall Survival in Metastatic Clear Cell Renal Cell Carcinoma

Abstract: Immune infiltration is typically quantified using cellular density, not accounting for cellular clustering. Tumor-associated macrophages (TAM) activate oncogenic signaling through paracrine interactions with tumor cells, which may be better reflected by local cellular clustering than global density metrics. Using multiplex immunohistochemistry and digital pathologic analysis we quantified cellular density and cellular clustering for myeloid cell markers in 129 regions of interest from 55 samples from 35 patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Most hypothesized mechanisms for the M2-like TAM pro-tumor effect rely on close proximity to their effector cell, and as such we aimed to associate measures of geospatial TAM clustering with clinical outcomes. Previous work by our group identified worse OS in patients with increased interface clustering of tumor cells and CD68+ TAMs, a pan-macrophage marker, in a small cohort of patients with metastatic ccRCC who subsequently received IT, further supporting the notion that TAM spatial distribution can affect outcomes 25 . In the present study, we identified more advanced clinical stage and substantially worse OS and CSS for patients with CD163+ M2-like TAMs clustered into the stromal compartment at the tumor-stroma interface.…”
Section: Namely Clustering Of M2-like Cd163+ Macrophages and Cd8+ T-cells Into The Stromal Compartment Atsupporting
confidence: 72%
See 1 more Smart Citation
“…Most hypothesized mechanisms for the M2-like TAM pro-tumor effect rely on close proximity to their effector cell, and as such we aimed to associate measures of geospatial TAM clustering with clinical outcomes. Previous work by our group identified worse OS in patients with increased interface clustering of tumor cells and CD68+ TAMs, a pan-macrophage marker, in a small cohort of patients with metastatic ccRCC who subsequently received IT, further supporting the notion that TAM spatial distribution can affect outcomes 25 . In the present study, we identified more advanced clinical stage and substantially worse OS and CSS for patients with CD163+ M2-like TAMs clustered into the stromal compartment at the tumor-stroma interface.…”
Section: Namely Clustering Of M2-like Cd163+ Macrophages and Cd8+ T-cells Into The Stromal Compartment Atsupporting
confidence: 72%
“…However, scRNA-seq methodologies are tissue-destructive, impeding the ability to analyze the effect of immune cell geospatial location and distribution. TAMs affect the TIME through a variety of receptor-binding and paracrine mechanisms that rely on proximity to their effector cells, and the specific location and geospatial distribution of TAMs has been shown to have a significant impact on their pro-tumor activity [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this group demonstrated greater expressions of inflammation-promoting and parainflammation factors as well as more intense type I Interferon (IFN) response, indicating a decreased autoimmunity function and a poor prognosis. If tumor-associated macrophages reveal a high infiltration, a poor OS in metastatic ccRCC could be expected [39]. In ccRCC patients, tumorinfiltrating mast cells secret IL-10 and TGF-β to decrease anti-tumor immunity, leading to a worse prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we used the localized segmented cell centres and a radius ] 25μ in order to quantify the number of immune cells. We chose this radius as a biologically relevant distance for interaction between tumour cells and immune cells [27]. Thus, we counted the number of the different immune cells that were identified within this radius of each segmented tumour cell.…”
Section: Three-dimensional Reconstruction and Spatial Analysismentioning
confidence: 99%